DECIDE: A Decision-Making Model for More Effective Decision Making by Health Care Managers. Issue 3 (July 2020) - Guo, Kristina L.
Abstract : The purpose of this article is to describe a step-by-step process for decision making, and a model is developed to aid health care managers in making more quality decisions, which ultimately determines the success of organizations. The DECIDE model is the acronym of 6 particular activities needed in the decision-making process: (1) D = define the problem, (2) E = establish the criteria, (3) C = consider all the alternatives, (4) I = identify the best alternative, (5) D = develop and implement a plan of action, and (6) E = evaluate and monitor the solution and feedback when necessary. The DECIDE model is intended as a resource for health care managers when applying the crucial components of decision making, and it enables managers to improve their decision-making skills, which leads to more effective decisions.